USING PHRASEOLOGISTS WHEN TEACHING PRONUNCIATION, GRAMMAR, VOCABULARY AND TRANSLATION (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Phraseologisms are an integral part of the Russian language, giving it brightness, imagery and expressiveness. These stable combinations of words reflect the culture, history and worldview of the people, allowing complex meanings to be conveyed with the help of bright and concise turns of phrase. In this article we will look at the main characteristics of phraseological units, their role in the language and features of use.